Explaining individual differences in cognitive performance: The role of anxiety, social support and living arrangements during COVID-19. (November 2022) - Edwards, Elizabeth J.; Zhang, Xiaohan; Chu, Khanh Linh; Cosgrove, Louise K.; Vaughan, Robert S.
Abstract: The present study investigated the relationship between anxiety, social support, living arrangements and cognitive performance of university students during the global pandemic. Two hundred and fifteen students participated by completing online questionnaires. Separate moderated multiple regression models were used to test whether social support (Family, Friends, Significant Other subscales of the Multidimensional Scale of Perceived Social Support) moderated the relationship between anxiety (Anxiety subscale of Depression, Anxiety Stress Scale), living arrangements (Living Alone vs Living with Friends and Family) and cognitive performance (Cognitive Failures Questionnaire), after controlling for comorbid depression. The results for each level of perceived social support suggested that anxiety was negatively associated with cognitive performance. Our most significant finding was that for students living alone, social support from a significant other offered a protective factor, whereby buffering the anxiety related cognitive deficits prevalent in those who reported lower social support. These data have important practical implications for supporting the social-emotional and academic needs of university students during the global pandemic. Highlights: Anxiety was significantly and negatively associated with cognitive performance. Social support from a significant other can buffer anxiety-related performance deficits. Implications for supporting students studying during the pandemic are discussed.